PERHITUNGAN STRUKTUR BETON BERTULANG PADA PEMBANGUNAN HOTEL 7 LANTAI DI JALAN AHMAD YANI 2 KABUPATEN KUBU RAYA: PERHITUNGAN STRUKTUR BETON BERTULANG PADA PEMBANGUNAN HOTEL 7 LANTAI DI JALAN AHMAD YANI 2 KABUPATEN KUBU RAYA - Khairunnisa, Hafidza Ulfa; rasiwan, rasiwan; supardi, iwan (RETENSI, 2021)
Increasing growth of economic in developing product and services that currently happened in kubu rayadistrict encourage development of hotel planning.Development of 7th floor hotel building in Ahmad Yani street is expected to increase economy, technology access,unisolated the area, increase mobility and social contacts of the community activities.Kubu Raya district is a soft soil area, that is why construction analysis in hotel building needed, todevelopment of reinforced concrete hotel, it is expected the building fill the safety factor and comfiness. Theanalysis did to fulfil that aspect with the applicable regulation such as dead load which refers to the LoadingPlanning Guidelines for Houses and Buildings 1987, Indonesian National Standard 1727:2013 used to analyzewind loads and live loads on buildings, Indonesian National Standard 1726:2019 used to analyse earthquake loadlike define the site class, seismic design coefficient, also seismic force resisting system. Indonesian NationalStandard 2847:2013 used to design construction material that will used in preliminary design of structuralelement, concrete covers, also formula used from slab, beam, column, and foundation. Increasing growth of economic in developing product and services that currently happened in kubu rayadistrict encourage development of hotel planning.Development of 7th floor hotel building in Ahmad Yani street is expected to increase economy, technology access,unisolated the area, increase mobility and social contacts of the community activities.Kubu Raya district is a soft soil area, that is why construction analysis in hotel building needed, todevelopment of reinforced concrete hotel, it is expected the building fill the safety factor and comfiness. Theanalysis did to fulfil that aspect with the applicable regulation such as dead load which refers to the LoadingPlanning Guidelines for Houses and Buildings 1987, Indonesian National Standard 1727:2013 used to analyzewind loads and live loads on buildings, Indonesian National Standard 1726:2019 used to analyse earthquake loadlike define the site class, seismic design coefficient, also seismic force resisting system. Indonesian NationalStandard 2847:2013 used to design construction material that will used in preliminary design of structuralelement, concrete covers, also formula used from slab, beam, column, and foundation. Structural analysis of reinforced concrete 7th floor hotel building in Ahmad Yani 2 street resulting slabthickness with 12 and 10 cm, beam with 35x 70 cm, 30 x 50 cm, 25 x 45 cm, 15 x 30 cm, 2 type of column withsize 70 x 70cm, 30 x 30cm also distributed to Pile Cap with 5 spunpile diameter 50 cm.